Comportamento sexual de risco após diagnóstico de sífilis - Oliveira, Lorena Guimarães (2023)
OBJECTIVE: To analyze the sexual behavior of risk of clients after diagnosis of syphilis. METHODOLOGY: This is an exploratory and descriptive study, with a quantitative approach with qualitative complementation. The study was conducted in Fortaleza in a Primary Health Care Unit. The study population consisted of 42 users. The interview script was divided into two parts: the first with the following data: age, sex, education, marital status, family income and occupation; and the second with fundamental questions regarding sexual behavior after the diagnosis of syphilis. Results and Discussions: There was a predominance of females (62%), aged over 24 years (76%), with up to 09 years of schooling, most of them declared themselves married or single (90%) and declared themselves brown or white. The beginning of sexual life between 10 and 14 years were 50% of the participants, 64.28% had relationships with more than ten partners and at the time of application of the study 80.95% maintained sexual relations, of these 73.80% maintained only one partner at the time and most with stable partnerships. The use of illicit drugs before sexual intercourse is less prevalent than alcohol use. Of the interviewees, 57.14% used condoms sometimes and 26.19% never used condoms. Thus, we can observe through the study that the greater the lack of education and unemployment, the greater the conditions of vulnerabilities. The use of alcoholic beverages and drugs has always been a very worrying factor when related to sexual relations, and the use of these substances before sexual intercourse can result in multiple partnerships and unprotected sex, that is, without condom use. When asked about the feelings that were generated, the answers fit into four aspects: the ignorance about the disease, the fear generated with the diagnosis of the disease, the concern to affect the baby during pregnancy and the feeling generated in the concern to have acquired the partner's disease. CONCLUSION: The expansion of users access to education and health services with prevention, protection and treatment in a group is necessary. The offer of services related to access to rapid tests, appropriate treatments and means of prevention made available optimally and without bureaucratic barriers complements the line of care in the field of sexual health.